Optimization of Mixed Fluid Cascade Natural Gas Liquefaction Plant Feed Stream Pressure - Ikonnikova A. Yu.; Baranov A. Yu.; Kravchenko D. V.; Seredenko E. S. (Problems of the Regional Energetics)
This paper presents the results of a study on optimising the feed stream pressure of the Mixed Fluid Cascade natural gas liquefaction cycle. The objective is to optimise the pressure of the feed stream to distribute heat effectively over the cooling stages and reduce the energy cost of the cycle. To achieve the goal, the following tasks have been done: constructing the mathemati-cal model of the cycle, performing the calculation experiment for different values of the feed stream pressure to determine energy characteristic values, and determining the optimal values of feed stream pressure. The flow characteristics of the working substances in the cycle are deter-mined based on the Peng–Robinson–Stryjek–Vera equations of state and Benedict–Webb–Rubin. The mass flow of the working substance is calculated for each cycle's stage heat load, at both constant and different values of the working point temperatures. The distribution of heat load for liquefying 1 kg of natural gas by stages is displayed, and achievable working point tem-peratures of the feed flow are determined. The energy consumed by the compressor units and the amount of compression heat dissipated are calculated. The study's main finding is that the optimal feed pressure in the Mixed Fluid Cascade cycle is higher than the standard pressure. The significance of the obtained results lies in the significant reduction of energy costs of the Mixed Fluid Cascade cycle at a feed stream pressure of 13 MPa.